Analisis Ketimpangan Pendapatan Antar Kabupaten/Kota Di Provinsi Nanggroe Aceh Darussalam - Yurina, Yurina (Universitas Malikussaleh, 2013)
This article examines what regional inequality rate, and the effect of regional economic growth in Nanggroe Aceh Darussalam (NAD) Province. Time series data is applied from selected edition by BPS, covering 21 regency/city in NAD Province during 15 years period, 1990-2005. By using Williamson Index, inquality regional income index below 1, however, it fluctuate each year, particularly inquality Dana Perimbangan, labor participation and education. The effect of economic regional growth to inequlaity regionalÂ is significant -0,01577, increasing economic regional growth it will reduce inquality regional index 0,01577. Hence, we recommended that firstlly, in short-run policy expand the labor intensive for agriculture and small-scale industry and secondly, in the long-run policy, develop capital intensive for export-oriented commodity or product.